2022
DOI: 10.1186/s12887-022-03808-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between smartphone addiction and aggression among Lebanese adolescents: the indirect effect of cognitive function

Abstract: Background Despite a large body of research has shown that smartphone addiction (SA) is associated with aggressive behaviors, only a few mediators have been previously examined in this relationship among early adolescent students. No previous studies have explored, to our knowledge, the indirect role of cognitive function despite its great importance during this life period. This study is intended to verify whether cognitive function have indirect effects on the relationship between SA and aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…Buss-Perry Aggression Questionnaire-Short Form (BPAQ-SF). This questionnaire, validated in Lebanon [34], was used to assess the level of aggression of an individual [4,26]. It is a self-report tool consisting of 29 items such as "If I have to resort to violence to protest my rights, I will", "I have threatened people I know" and "When people annoy me, I may tell them what I think of them".…”
Section: Methodsmentioning
confidence: 99%
“…Buss-Perry Aggression Questionnaire-Short Form (BPAQ-SF). This questionnaire, validated in Lebanon [34], was used to assess the level of aggression of an individual [4,26]. It is a self-report tool consisting of 29 items such as "If I have to resort to violence to protest my rights, I will", "I have threatened people I know" and "When people annoy me, I may tell them what I think of them".…”
Section: Methodsmentioning
confidence: 99%
“…It has also been shown that there is a direct correlation between aggression and a poor maternal relationship or low self-esteem [ 2 ]. Moreover, technologies, such as smartphones, contribute to an increase in violence, as does the consumption of aggressive video games [ 7 ].…”
Section: Introductionmentioning
confidence: 99%